Neuroactive drugs inhibit trypsin and outer membrane protein processing in Escherichia coli K-12. - Gayda, R C (1979)
Previous studies demonstrated that a cloned 2-megadalton (MDal) fragment of Escherichia coli DNA contained the structural gene for major outer membrane protein a (also known as 3b or M2 (40 kDal). The present study demonstrates that M2 is synthesized from a 42-kDal precursor that also is present in the outer membrane. The conversion of the 42-kDal precursor to M2 is inhibited by a number of different local anesthetics (procaine, piperocaine, lidocaine, cocaine), by the neuroactive drug atropine, and by the classical trypsin inhibitors N alpha-tosyllysine chloromethyl ketone (TLCK) and benzamidine. Our kinetic studies demonstrate that the amidase action of pure trypsin is inhibited competitively by the local anesthetics tested (excluding lidocaine) as well as by atropine and neostigmine. A mechanism of action for local anesthetics as well as atropine in E. coli may to be inhibit trypsinlike proteases, in a competitive manner, in the region of the outer membrane. The mechanism of action of these compounds in regulating nerve conduction in man have certain features in common with the mechanism proposed in E. coli.